MOTIVES OF BULLYING PERPETRATORS IN THE ANALYSIS OF THE INTERPRETATION OF SURAT AL HUJURAT VERSE 11 PERSPECTIVE PSYCHOLOGY OF SIGMUND FREUD - Luluk Masruroh (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research is a study of the term verse bullying which is then dissected through the perspective of the Koran and psychology. Interest in conducting this research was based on the understanding that a verse whose editorials are too universal to be applied in everyday life. In addition, what if the verse is analyzed through the perspective of mufassir and psychology. The formulation of the problem in this research is; 1) how is bullying in surah al-Hujurat verse 11? 2) What is the relevance of bullying according to the Koran and psychology? This type of research is a type of library research or Library Research, of course it has two kinds of sources, namely primary sources and secondary sources. The primary source is psychology books by Sigmund Freud, Karen Horney, and Erich Fromm. While the secondary source is in the form of commentary literature, articles, journals and other scientific works that support this research. The conclusion of this research is the values ​​of anti-bullying education in the Al-Qur'an Surah Al-Ḥujurāt verse 11 emphasizes how Muslims should treat their siblings by not hurting their bodies and hearts, by not making fun of, ridiculing, insulting. The values ​​of anti-bullying education also mean teaching people to avoid all forms of bullying towards others, because these actions violate the values ​​taught by the Al-Quran.